Investigation of radiation shielding characteristic features of different wood species. (March 2022) - Barman, Robin; Hossain, Md. Sayed; Das, Anik; Ahmmad Rabby, Md. Kaosar
Abstract: The radiation shielding properties of eleven wood species, namely Samanea saman, Albizia procera, Swietenia mahagoni, Mangifera indica, Gmelina arborea, Acacia auriculiformis, Artocarpus heteroPhyllus, Vachellia nilotica, Tectona grandis, Aegle marmelos and Syzygium cumini with varying densities, have been investigated using Phy-X/PSD to determine the mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), mean free path (MFP), half-value layer (HVL), tenth value layer (TVL) and fast neutron removal cross-section (FNRCS). The MAC of these woods has been determined using Phy-X/PSD program in the energy range from 1 keV to 10 5 MeV for total photon interaction. The validity of the Phy-X/PSD program was verified by comparing the results with those calculated by the XCOM and EpiXS programs. A very good agreement was observed among MAC values obtained by three programs. The MAC values were then used to estimate the LAC, MFP, HVL, and TVL. The highest MAC and LAC were observed at the lowest tested energy. The minimum MFP, HVL, and TVL occurred at the lowest energy, increased with increasing energy and decreased with increasing density, meaning that the woods with higher densities are more effective at lower energies. The obtained results showed that the Aegle Marmelos wood is the most effective for fast neutron attenuation whereas Mangifera Indica is the least effective. In all cases, the hydrogen element plays a major role in fast neutron attenuation. The results from this research point that radiation shielding is enhanced by the wood of appreciable density and woods, with rich in hydrocarbons and low Z materials, are more suitable for fast neutron attenuation and less suitable for photon attenuation. The present study would provide an insight for nuclear designers and justifies the usability of wood as shielding materials owing to their availability, low cost, and non-hazardous behavior. Highlights: Photon and neutron shielding properties of woods with varying density were studied. Phy-X/PSD, XCOM and EpiXS codes were used to evaluate the gamma shielding parameters. Values obtained for mass attenuation coefficient by each code are in good agreement. Shielding parameters depend on wood densities and photon energies. The tested woods have better neutron protection features.